PERAN BIMBINGAN PERKAWINAN OLEH BADAN PENASIHATAN PEMBINAAN DAN PELESTARIAN PERKAWINAN (BP4) TERHADAP CALON PENGANTIN DI KANTOR URUSAN AGAMA PONTIANAK TIMUR - Munawar Rahim; Heri Triyana, Ubabuddin (CV. Adiba Aisha Amira, 2024)
Allah SWT created His creatures in pairs, male and female. Marriage is a religious call that must be carried out by humans for those who are able to start a family. There are many lessons that can be taken from marriage, one of which is that it can give birth to peace and happiness full of love. However, marriages do not always go as expected, with marriage guidance the prospective bride and groom receive direction and guidance before getting married, it is hoped that the prospective bride and groom can create a family that is sakinah mawadah and warahmah, and can reduce the divorce rate. The method used in this research is (field research), namely research in which data is obtained through interviews with several informants who have been selected and determined by the author. And this research is qualitative, namely research that produces descriptive data in the form of written or spoken words from people and observable behavior. Considering the importance of methods in research. Based on the results of the research, it can be concluded that, the provision of marriage guidance by BP4 KUA East Pontianak District to prospective brides and grooms is carried out on Thursdays on weekdays from 07.30 to 11.30 then carried out using the lecture method, Q&A for 2-3 hours. However, this plays an important role because of the guidance given to prospective brides and grooms to be able to create a sakinah mawadah and warahmah family, and reduce the divorce rate. The obstacles faced in carrying out marriage guidance include time constraints, discipline of the prospective bride and groom, collaboration with other agencies, staff shortages, unequal education of the prospective bride and groom, and other obstacles. The KUA of East Pontianak District carries out marriage guidance carried out by BP4 properly, and it is hoped that the prospective bride and groom can create a family that is sakinah mawadah warahmah.